Kegiatan Bimbingan Belajar dalam Meningkatan Kualitas Belajar Anak di Kelurahan Gunung Sari Ilir Balikpapan - Rahayu Sri Waskitoningtyas; Husnul Khotimah; Tri Hariyati Nur Indah Sari (Abdimas Universal, 2023)
The level of understanding and mastery of the material for each student is different. One of the efforts that parents have made so far is by involving their children in tutoring outside of school. This community service activity is a means of conveying the usefulness of knowledge and the lecturers' sense of concern for the community in the field of education in the form of tutoring assistance outside of school in the Gunung Sari Ilir sub-district, Balikpapan. This service is carried out at Mrs. Ika's Tutoring House. The subjects of the service were children who signed up for tutoring at the tutoring, while the objects interviewed were 5th grade elementary school students with purposive sampling as the sample. Methods of data collection by observation, interviews, and documentation. The data analysis technique is descriptive narrative. The results of this service explain that tutoring has such a big impact on students because through tutoring outside of school they can better understand lessons again. Non-formal education through tutoring is expected to increase students' interest in understanding lessons. Usually, students are invited to learn with different and more attractive methods or ways of teaching by introducing something new in tutoring. Students are not only required to memorize, but must understand and have an interest in the material being studied. So that each student will be more active in thinking and solving problems related to problems in school.